2019
DOI: 10.1002/jia2.25370
|View full text |Cite
|
Sign up to set email alerts
|

Global implementation of PrEP for HIV prevention: setting expectations for impact

Abstract: Introduction Questions remain whether HIV pre‐exposure prophylaxis (PrEP) can be translated into a successful public health intervention, leading to a decrease in population‐level HIV incidence. We use examples from HIV treatment and contraceptives to discuss expectations for PrEP uptake, adherence, and persistence and their combined impact on the epidemic. Discussion Targets for PrEP uptake must be based on the local HIV epidemic and will depend on appropriate estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…TFV‐DP DBS concentrations ≥700 fmol/punch, deemed to be protective from HIV for the preceding 30 days [42] in this study was found in 46% to 52% of participants at both three and six months, similar figures to those seen in US adolescent studies conducted between 2013 and 2014 (30% to 50%) at the same time points [21,35]. An earlier adolescent study in 2010 that saw protective levels of only 20% by six months [43], a trend of improved adherence in newer studies also observed in adult studies, presumed to be due to higher general knowledge in PrEP efficacy and better informed and more motivated study participants in PrEP studies [44,45]. The fact that all aforementioned studies including this study did not see any HIV seroconversions despite imperfect PrEP adherence may have been due to PrEP use being effectively used in an event‐driven fashion during risky events.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…TFV‐DP DBS concentrations ≥700 fmol/punch, deemed to be protective from HIV for the preceding 30 days [42] in this study was found in 46% to 52% of participants at both three and six months, similar figures to those seen in US adolescent studies conducted between 2013 and 2014 (30% to 50%) at the same time points [21,35]. An earlier adolescent study in 2010 that saw protective levels of only 20% by six months [43], a trend of improved adherence in newer studies also observed in adult studies, presumed to be due to higher general knowledge in PrEP efficacy and better informed and more motivated study participants in PrEP studies [44,45]. The fact that all aforementioned studies including this study did not see any HIV seroconversions despite imperfect PrEP adherence may have been due to PrEP use being effectively used in an event‐driven fashion during risky events.…”
Section: Discussionsupporting
confidence: 78%
“…This may be a more appropriate goal to aim for in adolescents where the expectation of perfect adherence may become a barrier for those who would otherwise benefit from PrEP [44,46]. We believe that in this study, a mix of few sex acts, use of alternate HIV protection methods such as condoms and reduced perceived risk of situations driven by incomplete neurocognitive development typical of the adolescence phase of growth contributed to the inconsistent PrEP use seen [44‐45,47]. This emphasises the need to combine PrEP with condoms and other HIV prevention modalities as a package to protect adolescents against HIV.…”
Section: Discussionmentioning
confidence: 96%
“…Several women reported missing doses of PrEP with more than 50% of participants reporting missing ≥ 2 doses over the prior 30 days, implying protection might have been inadequate as at least 6 doses a week are required for adequate protection in non-rectal HIV exposure [ 24 ]. Reasons for missing doses because participants forgot, were busy, and feared or experienced side effects have been documented in other studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-exposure prophylaxis is the newest of the technologies, and the first biomedical intervention for sexual prevention of HIV since condoms. Despite being approved for use in the USA since 2012, uptake has been low, and persistence lower still [ 111 ]. Alternative formulations and modalities of PrEP hold promise for overcoming some of the challenges with PrEP as a daily pill, such as adherence and persistence [ 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%